2008
DOI: 10.1007/s00167-008-0561-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous osteonecrosis of the knee involving both the medial femoral condyle and the medial tibial plateau: report of three cases

Abstract: Spontaneous osteonecrosis of the knee (SPONK) usually involves a single condyle or plateau. The medial femoral condyle (MFC) is most often involved and spontaneous osteonecrosis of the medial tibial plateau (MTP) is a rare condition, representing only 2% of all necroses reported in the knee. SPONK involving both the MFC and the MTP is extremely rare. SPONK occurring in either the MFC or the MTP individually might extend to the corresponding side of the knee in the advanced end-stage; however, in that situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, the aseptic loosening of the tibial component is a concern in this type of osteonecrosis because good bone quality is essential for reliable fixation of the tibial component [27]. When considering the size of the necrotic area, TKA would be a safer choice for larger areas rather than UKA [3, 10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the aseptic loosening of the tibial component is a concern in this type of osteonecrosis because good bone quality is essential for reliable fixation of the tibial component [27]. When considering the size of the necrotic area, TKA would be a safer choice for larger areas rather than UKA [3, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous osteonecrosis of the knee (SONK) in the medial tibial plateau was first reported by D'Anglejan et al in 1976 [1]; this is a rare condition compared to SONK in the medial femoral condyle, and it represents only 2% of all osteonecrosis cases reported in the knee [2][3][4][5]. Similar to SONK in the femoral condyle, most patients with osteonecrosis of the medial tibial plateau are women older than 60 years who have sudden pain onset on the medial side of the knee, which is often related to minor trauma or an increase in activity [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medial tibial condyle accounts for only 2% of the cases. 5 It typically affects older patients (usually > 50 years) with female predominance Magnetic resonance imaging is very sensitive and specific in diagnosing spontaneous osteonecrosis. Role of bone scan was variable in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study performed between January, 2005, and February, 2008, Jung et al 20 found that of 11,093 knees after total knee arthroplasty (TKA), three had SPONK in both the medial femoral condyle and the medial tibial plateau. Those three patients (mean age, 59 years; range, 55-63 years) had distinctive radiographic findings, including longitudinal subchondral collapse.…”
Section: Introductionmentioning
confidence: 99%